Meningkatkan Keterampilan Berbicara Menggunakan Metode Contextual Teaching and Learning Siswa Kelas XI SMK BSI - Putu Intan Kurnia (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2020)
The purpose of this Internship research aims to analyze: 1). speaking skills of XI Tourism Hospitality class students. 2). learning using the Contextual Teaching and Learning method which is carried out in class XI Hospitality Tourism so that students have good and correct Indonesian language skills. 3). how to improve students' speaking ability after the lesson using the Contextual Teaching and Learning method.Qualitative methods are used in the research approach undertaken. Where this qualitative research seeks to provide an explanation, describe, and outline the main issues that will be discussed in the study then draw conclusions deductively. Based on the results of the study indicate that the object of research is a number of 15 students of this study from pre-cycle to cycle 1 shows that there is an increase in the average value of students that is 64.33 to 73.67. While from pre-cycle to cycle 2 shows that there is an increase in the average value of students that is 64.33 to 78. From the results above indicate that there has been a change from pre-cycle to cycles 1 and 2. These conditions indicate that there has been a change the value of students who showed an increase in students' abilities since using the CTL method. So from here it shows that the application of the CTL method has a good impact on improving students' ability to speak.